Círculos de cultura no Rio Grande do Sul : um movimento de alfabetização realizado a partir de Paulo Freire (1963-1964) - Dalsotto, Mariana Parise Brandalise (My University, 2022)
The present thesis, linked to the research area of History and Philosophy of Education of the Graduate Program at the University of Caxias do Sul, aimed at analyzing the historical context and the constitution of culture circles in Rio Grande do Sul mediated by the presence of Paulo Freire (and from there) between the years 1963 and 1964. The methodology used was the historical documentary analysis of newspapers such as Correio do Povo, Jornal do Dia, and Diário de Notícias, as well as the analysis of interviews, which were carried out using the Oral History methodology. Through the theoretical support of the History of Education and Cultural History, I mobilize concepts such as representation, cultural mediators, mediating intellectuals, and literacy. The categories constructed with the analysis were: (i) mobilization (which I expressed as the organization and realization of the training course for debate coordinators, held in Porto Alegre), (ii) action (from which I observed the practices of culture circles carried out in the State) and (iii) the interruption and silencing (occurred after the beginning of the civil-military regime). Initially, I accomplished a theoretical study (i) to know historical aspects of education in Brazil and Rio Grande do Sul in the 1950s and 1960s, (ii) to deepen the centraltheme of the thesis through authors who reflect on it, in addition to Paulo Freire himself and (iii) to investigate the theoretical-methodological framework. Having followed this research path, the thesis that I defend with this narrative is that between the years 1963 and early 1964, in the context of the effervescence of social movements and popular culture focused on Education, in Brazil and Rio Grande do Sul, some people from that state moved around the country to get to know and appropriate themselves of the cultural circles that established how the literacy program based on and proposed by Paulo Freire was organized, which started to be propagated nationally. Subsequently, these people - teachers, but primarily university and high school students, characterized here as mediating intellectuals - guided by the State Department of Education and Culture, spread out Freires ideals for literacy through their sociability network in Porto Alegre (the state capital) and some other cities in the interior of the state, constituting representations and finding ways of putting them into practice. These new representations were transcribed in the form of dissemination and execution of training for debate coordinators, initially based in Porto Alegre and with the pontual presence of Paulo Freire - but also programmed in other cities in the interior, from intellectual mediators of the State - as well as in the form of pilot experiments carried out, which confirm the effectiveness of culture circles in Rio Grande do Sul before the civil-military regime. When this happened, the most widespread representations about the literacy program became its criticisms, which ended up generating its silencing. [resumo fornecido pelo autor]
A presente tese vinculada à linha de pesquisa História e Filosofia da Educação do Programa de Pós-Graduação da Universidade de Caxias do Sul objetivou analisar o contexto histórico e a constituição dos círculos de cultura, no Rio Grande do Sul mediados pela presença de Paulo Freire (e a partir dela) entre os anos de 1963 e 1964. A metodologia utilizada foi a análise documental histórica de jornais como Correio do Povo, Jornal do Dia e Diário de Notícias, bem como da análise de entrevistas realizadas mobilizando a metodologia da História Oral. Por meio do apoio teórico da História da Educação e História Cultural, mobilizo conceitos como representação, mediadores culturais, intelectuais mediadores e alfabetização. As categorias construídas com a análise foram: (i) a mobilização (a qual expressei como sendo a organização e a realização do curso de formação de coordenadores de debates, realizado em Porto Alegre), (ii) a ação (a partir da qual observei as práticas dos círculos de cultura realizadas no Estado) e (iii) a interrupção e os silenciamentos ocorridos após o início do regime civil-militar). Realizei, inicialmente, um estudo teórico para (i) conhecer aspectos históricos da educação no Brasil e no Rio Grande do Sul nas décadas de 1950 e 1960, (ii) aprofundar tema central da tese por intermédio de autores que refletem sobre o tema, além do próprio Paulo Freire e (iii) estudar o referencial teórico-metodológico. Tendo percorrido esse caminho de pesquisa, a tese que defendo com essa narrativa é de que entre os anos de 1963 e início de 1964, no contexto de efervescência de movimentos sociais e de cultura popular voltados para a Educação, no Brasil e no Rio Grande do Sul, algumas pessoas desse Estado transitaram pelo país para conhecer e se apropriar dos círculos de cultura que estabeleciam a forma na qual se organizava o programa de alfabetização fundamentado e proposto por Paulo Freire, o qual passava a ser propagado em nível nacional. Na sequência, essas pessoas - professores, mas primordialmente estudantes universitários e secundaristas, aqui caracterizados como intelectuais mediadores - orientadas pela Secretaria de Educação e Cultura estadual, disseminaram os ideais freireanos para a alfabetização através de suas redes de sociabilidade, em Porto Alegre (capital) e em algumas outras cidades do interior, constituindo representações, ou seja, modos de colocá-los em prática. Essas novas representações foram transcritas na forma de divulgação e execução de formações para coordenadores de debates, inicialmente sediadas em Porto Alegre e com a presença pontual de Paulo Freire - mas também programadas em outras cidades do interior, a partir de intelectuais mediadores do Estado - bem como na forma de experiências-piloto realizadas, que confirmam a efetivação dos círculos de cultura no Rio Grande do Sul, antes do regime civil-militar. Quando este ocorreu, as representações acerca do programa de alfabetização mais difundidas passaram a ser as suas críticas, o que acabou gerando o seu silenciamento. [resumo fornecido pelo autor]
Keywords: Educação - Filosofia; Cultura - Rio Grande do Sul - História; Alfabetização; Freire, Paulo, 1921-1997; Educação - Rio Grande do Sul; Education - Philosophy; Culture - Rio Grande do Sul (Brazil) - History; Literacy; Education - Rio Grande do Sul (Brazil)